Snow play : how to make forts & slides & winter campfires plus the coolest Loch Ness monster and 23 other brrrilliant projects in the snow - Ralston, Birgitta (New York : Artisan ; Godalming : Melia [distributor], 2010)
With crazy creatures to build, challenging games to play, and outrageous spaces to sculpt, author Birgitta Ralston, a Europe-based designer, has imagined the most creative ways to play in the snow.
Keywords: Snow in art; Snow sculpture